Clinical, pathological, and radiological features of 80 pediatric diffuse intrinsic pontine gliomas: A single-institute study - Zhang, Peng; Duan, Yunyun; Gu, Guocan; Qu, Liying; Xiao, Dan; Xi, Tianshu; Pan, Changcun; Liu, Ya’ou; Zhang, Liwei (Frontiers in Oncology, 2023)
Objective: DIPGs were rare but devastating diseases. This retrospective cross-section study aimed to investigate the clinical, radiological and pathological features of DIPGs. Materials and methods: Clinical data of 80 pediatric DIPGs under clinical treatment in Beijing Tiantan Hospital from July 2013 to July 2019 was retrospectively collected and studied. Follow-up evaluation was performed. Results: This study included 48 males and 32 females. The most common symptoms were cranial nerve palsy (50.0%, 40/80 patients) and limb weakness (41.2%, 33/80 patients). Among the 80 patients, 24 cases were clinically diagnosed, 56 cases were pathologically verified and 45 cases were tested for H3K27M mutation status with 34 H3K27M positive cases. Radiological results indicated that enhancement was common (65.0%, 52/80 patients). Cho/Cr was of predictive value for H3K27M mutation status (P=0.012,Cut-off Value=2.38, AUC=0.801). Open cranial surgery followed by further chemotherapy and radiotherapy were benefit for patients’ better overall survival. Cox regression analysis indicated H3K27M mutation to be the independent prognostic influencing factor for DIPGs in this series (P=0.002). Conclusion: DIPGs displayed a wide spectrum of clinical and imaging features. Surgery applicable patients could get benefit from postoperative comprehensive therapy for a better overall survival. H3K27M mutation was the independent prognostic influencing factor for DIPGs.